Study of interfacial reactions between lead-free solders and immersion silver finish - Oshaghi, Safoura (2008)
Due to environmental considerations the use of lead-free solders has become common in electronic packaging industry. Among various lead-free solders available, near-eutectic Sn-Ag-Cu alloys are considered the most promising replacement of Sn Pb solders, and are widely used as lead-free solutions for ball-grid-array (BGA) interconnects in the microelectronic packaging industry. Among the various surface finishes available, electroless nickel/immersion gold (ENIG) is the most appealing at the moment. However, because of their black pad problem, immersion silver is being considered as an alternative surface finish. Doping elements such as Ni in solder alloys may lead to an increase in the undercooling during solidification thus affecting the growth of intermetallics. This project is carried out to investigate the intermetallics (IMC) formation during soldering between lead-free solders (Sn-3.0Ag-0.5Cu, Sn-3.0Ag-0.5Cu-0.1Ni, Sn-3.0Ag-0.5Cu-0.05Ni, Sn-3.5Ag and Sn-0.75Cu) and Immersion Silver surface finish, using solder size of 500 m. Top surface morphology and EDX (Energy-Dispersive X-Ray) results show that there are basically two types of intermetallics that were formed. Isothermal aging up to 2000 hrs results in larger and coarser IMCs. Also observed were the thickness of intermetallics that increased along with the aging time. In addition the present study also confirmed that doping SAC solders with small amounts of Ni caused finer microstructures compared to SAC305 solder without Ni doping element, resulting in thinner IMC s and smaller grain sizes.